THE CONTRIBUTION OF THE FOUNDERS OF THE JADIDIST MOVEMENT IN BUKHARA AT THE BEGINNING OF THE 20TH CENTURY - Safarova Gulzoda Ismailovna (International Journal of Literature and Language Studies, 2026)
Abstract. This article analyzes the formation of the Jadidist movement in the Bukhara Emirate at the beginning of the 20th century and its reform activities in the field of education. The article examines the role of the leading representatives of the movement - Mahmudkhodja Behbudiy, Abdurauf Fitrat, Sadriddin Ayniy and others - in organizing Jadid schools, creating textbooks and awakening national consciousness. Based on scientific sources, archival documents and modern research, it is proven that the reforms of the Jadidist movement in the field of education were an important factor in the modernization of Bukhara society.